An OD-characterizable class of simple groups - Akbari, M.; Chen, X.Y.; Moghaddamfar, A.R. (Algebra and Discrete Mathematics, 2020)
It is proved that nonabelian finite simple groups S with max π(S) = 37 are uniquely determined by their order and degree pattern in the class of all finite groups.